Relationship Between Parental Social Support and Student Academic Self Efficacy - Mawaddah Nasution; Khairani Khairani (Jurnal Neo Konseling, 2019)
Social assistance for students who provide assistance with good and positive forms and attitudes can help their development tasks, so that students care more about the environment for their parents. In fact there are still students who have not received good social support from followers who do not need to go to school and pull out the teaching and learning process, students are bullied because students' clothes and pants are not suitable to be used again, students imitate assignments, students cannot support in the classroom. This study aims to improve social support and self-efficacy of academic students in order to be able to support daily life effectively and be able to achieve the desired goals. This research is a kind of descriptive correlational research with quantitative methods. The number of samples is 184 students selected using the Stratified Proportional Random Sampling technique. The research instrument used was a social assistance questionnaire and student academic self efficacy questionnaire. The results of the study revealed that (1) the social support of the parents in Padang Public Middle School 4 in the category was sufficient to support (2) the self efficacy of students in Padang Middle School 4 in general in accordance with the category quite confident. (3) There is a significant relationship between social support and self efficacy of students in Padang N 4 Middle School. Based on the research findings, the role of guidance and counseling services in social support assistance related to information and counseling services is needed.